DEVELOPMENT OF A MODEL FOR PREDICTING ELECTRICAL ENERGY DEMAND AT PT. PLN (PERSERO) ULP BANGKO: PENGEMBANGAN MODEL UNTUK PREDIKSI KEBUTUHAN ENERGI LISTRIK DI PT. PLN (PERSERO) ULP BANGKO - ARDHANA, NABILA (Institut Riset dan Publikasi Indonesia, 2024)
Enhancing the sustainability and efficiency of electricity consumption has become a primary focus in energy resource management. In this context, developing electricity demand forecasting models is of paramount importance. This research aims to develop an effective and accurate model for predicting electricity demand based on historical data across various sectors of society. The methods to be employed include simple linear regression, time series analysis, and exponential smoothing, which will be visualized using Visual Basic. Based on historical data from PT. PLN (Persero) ULP Bangko from 2013 to 2023, it is recorded that there are 958,598 installed customers with various electricity tariffs and a total installed capacity of 1210.2 MVA. Research findings indicate a potential increase of 105.64% in installed capacity and 90.88% in the number of customers over the next 20 years.